2017
DOI: 10.1088/1361-6455/aa7098
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ionisation of polyatomic molecules in intense laser pulses is due to energy upshift and field coupling of multiple orbitals

Abstract: We present the results of a combined experimental and numerical study on strong-field ionisation of acetylene performed with the aim of identifying the mechanism behind the previously reported surprisingly large multi-electron ionisation probabilities of polyatomic molecules. Using coincidence momentum imaging techniques and time-dependent density functional simulations, we show that the reported efficient ionisation is due to the combined action of a significant geometrically induced energy upshift of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Since its first prediction [11], enhanced ionisation has been calculated and measured in myriad systems. These include diatomic [12,13] molecular species such as H 2 [14][15][16][17][18][19], I 2 [20][21][22][23], and Cl 2 [24], tri- [17,25,26] and polyatomic molecules [27,28]. It has also been used as a means to highlight electron nuclear coupling of degrees of freedom in photoelectron holography [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its first prediction [11], enhanced ionisation has been calculated and measured in myriad systems. These include diatomic [12,13] molecular species such as H 2 [14][15][16][17][18][19], I 2 [20][21][22][23], and Cl 2 [24], tri- [17,25,26] and polyatomic molecules [27,28]. It has also been used as a means to highlight electron nuclear coupling of degrees of freedom in photoelectron holography [29].…”
Section: Introductionmentioning
confidence: 99%
“…Nearly degenerate coupled charge-resonant states that occur for large inter-nuclear separations also facilitate a strong population transfer to the continuum [11,15,33]. On the other hand, for extended systems, multielectron and non-adiabatic effects play an increasingly important role [28,34,35] (for a recent review see [36,37]). Loosely speaking, non-adiabaticity implies that the electron probability density as a function of time does not 'follow' the field gradients, and instead may be related to population trapping, resonances, multielectron effects and coupling of different degrees of freedom.…”
Section: Introductionmentioning
confidence: 99%
“…This enhancement process is mediated by the stretching motions of the CH-bonds and occurs at bond lengths, which are about twice as large as the equilibrium value 18,19 . Recently, Erattupuzha et al found that CREI in acetylene originates not only from coupling of two states but rather due to an energy upshift and field coupling of multiple orbitals 20 . Following this argument, EI in complex molecules such as acetylene is not limited to a single critical inter-nuclear distance but can include a broader range of inter-nuclear distances, which are possibly assumed during a longer time interval during molecular motion initiated by, e.g., the ionization of the neutral molecule.…”
Section: Introductionmentioning
confidence: 99%
“…For an accurate description of the correlation effects we take orbitals with higher m-quantum numbers as described in Eq. (12) and in the present calculations we have considered up to m = ±1 which produces a converged EI results. In Ref.…”
Section: A Two-electron H2 Moleculementioning
confidence: 92%
“…EI describes the phenomenon that when a molecule is exposed to a strong laser field, the ionization probability increases significantly at certain critical internuclear separations. This enhancement is also known as charge-resonance enhanced ionization and has been studied extensively both experimentally [5][6][7][8][9][10][11][12] and theoretically [13][14][15][16][17][18]. The quantum mechanical study of simple diatomic molecules with double-well potentials leads to many interesting features which are absent in atomic processes.…”
Section: Introductionmentioning
confidence: 99%